Conflito civil e liberdade: o antagonismo de desejos como fundamento da liberdade republicana em Maquiavel - Winter, Lairton Moacir (2010)
The purpose of this work consists of analyzing the place that the big s and people s conflict occupies in Machiavelli s political thought and to investigate its relationship with the political freedom. More specifically, is the understanding of the concept of republican freedom giving special attention to his theory of the humors. The central hypothesis is that the freedom can only be reached by a balance point among the forces in conflict. For that, it is necessary that the conflict, not being annulled, be rationally regulated and normalized by the republican institutions, changing from negative force into force capable to converge in the State the commonwealth, the social order and the freedom of the whole political body. The republican law, born of the permanent confrontation of the antagonistic desires, subverts the negative character of the humors of big and people and it channels the force for the political life, demanding active citizenship of their members, it means, the participation of both humors in the public space as political agents for the maintenance of the freedom. To make it clear, we analyzed, firstly, the position of the tradition and the perspectives of the republicanism towards the problem of the political conflict in order to verify the republican elements present in Machiavelli s political thought. In a second moment, we tried to demonstrate the characteristics of the conflict of the humors, in agreement with those which the desire of the big gets confused with a desire of power, while the desire of the people is associated to freedom. In this perspective, we sought to elucidate the meaning of the good and the bad conflicts for the political life. Afterwards, we tried to highlight the need and the importance of the continuous foundation and re-foundation of the freedom front to the corruption of the republic, resulting from the homogenization of the manners of wanting of the humors in conflict. And, finally, we presented the dynamics of the conflict of the humors of big and people in the civil principality. In this regime, Machiavelli presents the conflict much more in the context of the political alliances than properly in relation to the freedom. From this point of view, we sought to demonstrate that in the civil principality the conflict is thought by Machiavelli not from the optics of the freedom, what is possible only in the republic, but from its role in the conservation and in the maintenance of the prince s power. For this reason, we tried to defend the theory of the republicanism of Machiavelli, according to the true political freedom is only possible when the antagonistic humors can relieve their desires through the participation in the public space of debates and collective decisions, what can only happen in a republican regime.